Relationship between insecure attachment and mobile phone addiction: A meta-analysis. (August 2022) - Zhang, Yiming; Ding, Yueming; Huang, Haitao; Peng, Qianwen; Wan, Xiao; Lu, Guangli; Chen, Chaoran
Highlights: A significant association between insecure attachment and mobile phone addiction. Attachment anxiety is more related with mobile phone addiction than attachment avoidance. Gender and attachment measures did not moderate this relation. Mobile phone addiction measures moderate this relation. Abstract: Objective: Many studies have explored the relationship between insecure attachment and mobile phone addiction from different theoretical perspectives; however, the results have been different. This meta -analysis aimed to explore the relationship between insecure attachment and mobile phone addiction. Methods: Studies published before November 2021 were identified through a systematic online search. A total of 22 studies, including 38 independent effect sizes were included from a systematic search of multiple databases, with a total sample size of 11, 810 cases. Stata Version 16.0 was used for meta -analysis. Results: The meta -analysis based on random-effects model showed that mobile phone addiction was highly positively associated with attachment anxiety ( r  = 0.395, 95%CI [0.345, 0.442]) and weakly positively correlated with attachment avoidance ( r  = 0.194, 95%CI [0.137, 0.250]). The relationship between attachment anxiety and mobile phone addiction and that between attachment avoidance and mobile phone addiction were both moderated by mobile phone addiction measures but not moderated by gender and attachment measures. Conclusion: There is a positive correlation between mobile phone addiction and insecure attachment. In the future, measures to prevent mobile phone addiction should focus on insecure attachment individuals and help them construct a healthy attachment relationship and secure attachment model.